DEVELOPMENT OF A SETS-BASED E-MODULE ON ECOLOGY AND INDONESIA’S BIODIVERSITY FOR JUNIOR HIGH SCHOOL CLASS VII - Dwiningsih, Safrida; Wulandari, Sri; Mahadi, Imam (Universitas Bhinneka PGRI, 2026)
This study aims to develop an e-module based on the SETS (Science, Environment, Technology, Society) approach for the topic of Ecology and Biodiversity in Indonesia for Junior High School Class VII. The development utilized the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The e-module was designed to enhance students’ understanding of science concepts and foster environmental awareness through interactive, contextual, and real-life relevant learning. Validation results from content, pedagogical, and media experts indicate that the e-module is highly valid, with an average score of 0.95. Practicality tests with students and teachers also show very high practicality, with average scores of 91.61% and 98%, respectively. The e-module features interactive content through the Heyzine Flipbook platform, allowing multimedia integration such as videos and digital links. This research concludes that the SETS-based e-module is feasible to be used as an innovative teaching material that supports science learning and enhances students’ environmental awareness.